Emplacement in hostile spaces: hopeless notes – commentary to van Liempt - Aura Lounasmaa (Fennia: International Journal of Geography, 2023)
In her keynote lecture from the Finnish Geography Days in 2022 Ilse van Liempt offers a hopeful and useful approach to understanding refugees’ processes of belonging and home-making. She focuses on arrival infrastructures, which encompass both the formal and the informal processes and structures that greet migrants as they arrive. Important part of these is emplacement, where the focus can turn into how migrants themselves become part of creating arrival infrastructures and making home in new environments, including the public spaces they inhabit. My commentary draws from my experiences of the United Kingdom (UK) hostile bordering practices, and I am reminded that hostility, policing migration and migrants and bordering practices are not only present, but often framing both the formal and informal infrastructures. Secondly, I reflect on the meaning of home here: the patriarchal and heteronormative home can follow a migrant on their route, as well as become part of the bordering practice for new arrivals. Hence for some, home itself becomes a prison, a site of violence or a place of non-belonging. Finally, the emergence of the techno-borderscape (Godin & Doná 2020) has moved large parts of arrival infrastructures, both the bordering and the support that these represent, and possibilities of home-making online, with many migrants simultaneously having reduced access to the digital spaces.